A COMPARATIVE ANALYSIS OF TWO DIFFERENT SAMPLES OF SIDDHA CLASSICAL FORMULATION-PADIGALINGA CHENDURAM - Radhakrishnan, Meera; Kumarasamy, *Sivaranjani (International Journal of Ayurveda and Pharma Research, 2019)
Siddha is the traditional system of medicine in India which is practiced in southern part. This traditional system has many polyherbal and herbo-mineral formulation which is more effective but they lack standardization procedures. Standardization of a herbo- mineral formulation is essential to assess the quality, efficacy, purity and safety of the drug. The present paper deals with standardization of Padigalinga Chenduram, the Siddha formulation which is used for treating menorrhagia, diarrhoea, dysentry etc. In-house preparation and one marketed sample were subjected to standardization techniques like organoleptic study, physicochemical screening and heavy metal analysis. It was observed that both the samples differ in their organoleptic character, physicochemical analysis and heavy metal analysis like colour variance, percent weight loss on drying or moisture content was found to be less in market sample and total ash value was high as well. And the market sample was found to be better than the in-house sample in water-soluble and alcohol-soluble extractive values. The toxic heavy metals as per AAS is found in both formulations and the values are not matching with each other, and it may be due to the raw material collection time and geographical variation, etc. which can be further investigated for its pharmacological activity. More number of samples from different pharmas has to be studied to arrive at definite standard for manufacturing Padigalinga Chenduram. When a definite standard is arrived from future studies, Padigalinga Chenduram will be a cost effective Siddha formulation for the treatment of various ailments.